The structural model of sustainability: a discussion about elements, hierarchy and representation of the environmental system - Oppliger, Emilia Alibio; Ronda, Izabela Cristina Barbosa Prado de Souza; Oliveira, Ademir Kleber Morbeck de (Paisagem e Ambiente, 2020)
The concept of sustainability is based on three pillars: environmental, social and economic, all equally important, interdependent, with the goal of meeting human needs without degrading the environment, ensuring its preservation for future generations. However, it is necessary to understand how these pillars interact with each other. The objective was to review this concept and present a new structural model of sustainability, in which ‘ecological system’ is understood as nature without the human being. It is a theoretical article, based on the general theory of systems, referenced in critical analyses on sustainability and the relationship between nature, society and economy. It has been shown that the ecological system is the most important in representing sustainability, as it is self-regulating and does not depend on others. It is concluded that there is a hierarchy between the systems and that the environmental system is the sum of the ecological, socio-cultural and economic systems.